Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025. Issue 20 (18th October 2019) - Chen, Ming-Hong; Zhang, Wen-Long; Chen, Li; Lin, Ru; Xie, Yang; Fang, Dong-Sheng; Lian, Yun-Yang; Jiang, Hong
Abstract: Chemical investigation of a marine-derived actinomycete strain Verrucosispora sp. FIM06025 isolated from a marine sponge sample collected from the East China Sea, resulted in the discovery of two new alkaloids, (2-(hydroxymethyl)-3-(2-(hydroxymethyl)-3-methylaziridin-1-yl) (2-hydroxyphenyl) methanone (1 ) and 2-(1-hydroxyethyl)-3, 4-dihydrobenzo [ f ] [1, 4]oxazepin-5( 2H )-one (2 ). The structures of compounds1 and2 were determined by the detailed analysis of 1D, 2D NMR and HR-TOF-MS data, along with literature data analysis. The bioefficacy investigations revealed that compound1 exhibited a broad spectrum of antimicrobial activity with MIC (minimum inhibitory concentration) values ranging from 3.4 to 200 μg·mL −1 against H. pylori, P. aeroginosa, A. baumanniiin, E. coli and K. pneumonia, S. aureus, C. albicans and E. faecium, however, compound2, up to 200 μg/mL, displayed no antibacterial activity against these bacteria. Graphical Abstract: